Microbial Community Shifts in Response to Acid Mine Drainage Pollution Within a Natural Wetland Ecosystem - Aguinaga, OE (2018)
This work was financially supported in part by Ph.D. scholarship funding (to OA) from the National Council for Science, Technology, and Technological Innovation (CONCYTEC) of Peru and from the Faculty of Life Sciences, University of Manchester (to AD and JP).